Confounding effects of temperature in laser-induced fluorescence concentration measurements with iodine vapor. (21st October 2020) - Karthick, S K; Cukurel, B; Jacobi, I
Abstract: Laser Induced Fluorescence (LIF) provides a non-invasive, quantitative measurement of fluorescent tracers in complex mixing flows. The common availability of broad linewidth lasers and their use with iodine vapor tracers raises a significant concern about confounded tracer concentration measurements, due to the strong dependence of iodine fluorescence on both tracer concentration and flow temperature. We model the sensitivity of iodine fluorescent response to temperature fluctuations, especially for flows with significant temperature contrasts to ambient conditions, and establish a temperature uniformity requirement that bounds the relative error in tracer concentration measurements. We show that in a conventional laboratory setup, in order to bound the measured concentration error to about 5%, the relative temperature fluctuations in iodine LIF must be approximately an order of magnitude smaller than the desired measurement resolution of relative concentration fluctuations. Iodine LIF should thus be employed with great caution.